Potential of a virtual reality environment based on very-high-resolution satellite imagery for structural geology measurements of lava flows. (May 2022) - Jaud, Marion; Geoffroy, Laurent; Chauvet, François; Durand, Erwan; Civet, François
Abstract: Combining very-high-spatial resolution (<1 m) and the ability to provide stereo-pairs for 3D topographic reconstructions, Pleiades satellites offer great potential for large-scale and high-resolution studies in geosciences. In parallel, research-dedicated Virtual Reality (VR) applications are emerging based on high-quality data. We examined the potential of a VR application derived from very-high-resolution Pleiades imagery to infer the orientation of individual flows from kilometers-thick lava piles in the eastern Afar rift area (Stratoïd Formation, Djibouti). Based on Pleiades Digital Elevation Models and orthoimages, we compared two approaches: i) a "classical" method in "Mouse Mode" and ii) a method using the VR application. Both methods provide similar results in facet orientation measurements over the studied transects. Nevertheless, VR enables operator immersion in a very realistic virtual environment combining aerial synoptic and ground-level views. Our studied case shows the potential of those methods to get high-quality and unexpected structural information from an otherwise inaccessible environment. Highlights: 3D stereo-reconstruction of the Asal-Ghoubbet rift from Pleiades satellite imagery. Virtual environment derived from high-resolution Pleiades DEM and orthoimage. Quality control on virtual structural geology exploration and measurements. Large-scale virtual geological exploration.